Gas insufflation device for use with a lung ventilator - John Dingley (1997)
Inventor:DINGLEY JOHNApplicant:DINGLEY JOHN [GB]CPC:A61M16/00A61M16/0051A61M16/0075(+6)IPC:A61M16/00A61M16/08A61M16/10(+1)Publication info:GB2321599 (A)1998-08-05Priority date:1997-01-31